System for Visually Disabled through Wearables Utilizing Arduino and Ultrasound - Abdulkareem, Sabah A.; Mohammed, Hind I.; Mahdi, Abbas Alaa (Journal La Multiapp, 2024)
Blindness and other vision impairment is on the rise with more than 2.2 billion people worldwide are affected including children, elder persons, pregnant women, chronically ill and disabled persons who experience difficulties in mobility and being independent. Some of the conventional assistances like usage of white cane or a guide dog lacks the ability to cater all the needs of the blind people. The present research outlines a wearable system with Arduino and ultrasound equipment to improve the walking ability of the persons with vision impairment. From the use of the proposed system, there is the potentiality of detecting obstacles in real time and also determine the location hence minimizing the dependence on other help. The system consists of two wearable components: a glove and a belt which contain ultrasonic sensors, GPS module and GSM module and a vibration motor. The glove senses the objects that are in front of the user while the belt detects stairs or any other raised ground. The method used here was the development and calibration of these components separately then brought together to form a coherent entire system where all the component was precise and reliable. The findings show that the proposed system is successful to identify obstacles on its path before the user comes close to them and gives out alerts through sound and touch. GPS and GSM modules provide an extra layer of security to the kids by allowing a tracking of their location in real time.